2009
DOI: 10.1007/s12264-009-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxy stilbene glucoside reduces the cognitive impairment and overexpression of amyloid precursor protein induced by aluminum exposure

Abstract: Both TSG and VE significantly ameliorated the performance impairment in the passive avoidance task, and suppressed the over-expression of APP. Moreover, the effects of TSG, but not of VE, were in a time-dependent manner. Conclusion TSG may possess therapeutic effects against Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Ab is generated from APP via sequential cleavage by b-and c-secretases and the contents of Ab are related to the expression of APP, b-and c-secretases [44]. Chronic exposure to AlCl 3 through drinking water or food led to the overexpression of APP in the brain of rats [45,46]. Results from the present study indicate that the larger amounts of aluminum that accumulate in hippocampal and cortical neurons of AlCl 3 -deteriorated rat upregulated the expression of the APP and result in greater APP deposition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ab is generated from APP via sequential cleavage by b-and c-secretases and the contents of Ab are related to the expression of APP, b-and c-secretases [44]. Chronic exposure to AlCl 3 through drinking water or food led to the overexpression of APP in the brain of rats [45,46]. Results from the present study indicate that the larger amounts of aluminum that accumulate in hippocampal and cortical neurons of AlCl 3 -deteriorated rat upregulated the expression of the APP and result in greater APP deposition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to learning and memory tested in the passive avoidance task, the present results indicated that rats treated with aluminum lactate showed impaired performance in passive avoidance as evidenced by decreased step‐through latencies in the passive avoidance retention task. These recorded data are in accordance with results of several recent studies reported by Luo et al (2009), Bhalla et al (2010) and Ribes et al (2010). They all reported the ability of aluminum‐induced neurotoxicity to worsen memory functioning that was evidenced by impaired rats’ behavior in passive avoidance task.…”
Section: Discussionsupporting
confidence: 93%
“…THSG has antioxidant and anti-inflammatory activity [14][15][16][17]. Previous studies have shown that THSG can promote neuronal growth factor expression and improve learning and memory function in rodents [18][19][20]. Furthermore, THSG can protect from oxidative stress-induced neuronal degeneration and neurotoxicity in vitro, and in animal models of Parkinsonʼs disease and Alzheimerʼs disease [21][22][23].…”
Section: 354′-tetrahydroxystilbene-2-o-β-d-glucoside Attenuates Imentioning
confidence: 99%